Psychosocial impacts in populations exposed to solid waste facilities - Elliott, Susan J. (My University, 1992)
This thesis examines psychosocial impacts in three populations exposed to solid waste disposal facilities in southern Ontario. Psychosocial impacts are defined as a complex of distress, dysfunction and disability, manifested in a wide range of psychological, social and behavioural outcomes, as a consequence of actual or perceived environmental contamination. The scope of this research is based on the awareness and prevalence of exposure to environmental contaminants in Ontario, the relative absence of theory and empirical evidence to explain their determinants, and uncertainty as to ways to intervene effectively to reduce their adverse effects on human health and well-being. Three research objectives are addressed within a parallel case study design using descriptive and logistic regression analyses: (1) to determine the prevalence of psychosocial impacts among exposed individuals; (2) to investigate determinants of individual level psychosocial impacts; and, (3) to investigate the determinants of individual level actions taken in response to psychosocial impacts. Implicit across these objectives is the development of a clearer conceptual understanding of the nature and direction of the process of psychosocial impacts. The data come from an epidemiological survey of residents (N = 696) living within a prescribed radius from each of three solid waste facilities. The analytical model which guided the analysis was informed by a socioecological model of health and well-being and has three components: external variables (e.g., individual and exposure related variables), mediating variables (e.g., social network membership and involvement, health status measures as well as measures of general psychosocial health and well-being), and outcome variables (e.g., concern, effects and actions). Results show that levels of outcome reported vary by site. This finding indicates that the process of psychosocial impacts cannot be divorced from the community context within which they occur. Further, results for a series of site specific analyses show that outcome measures can be successfully explained by a combination of external and mediating factors. However, given the number and diversity of variable types emerging, there is no single cause and effect relationship operating. The implication is that strategies aimed to address and alleviate psychosocial impacts need to be specific to the characteristics of the populations in particular settings. Contributions made by the thesis are theoretical, development of a socioecological conceptual framework within the context of environmental stress theory; methodologic, development of an epidemiologic survey designed to measure psychosocial impacts; and substantive, analysis of the prevalence and determinants of psychosocial impacts
Keywords: Geography; Geography